If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(a + 1) + -3a = 54(29 + -1) Reorder the terms: 7(1 + a) + -3a = 54(29 + -1) (1 * 7 + a * 7) + -3a = 54(29 + -1) (7 + 7a) + -3a = 54(29 + -1) Combine like terms: 7a + -3a = 4a 7 + 4a = 54(29 + -1) Combine like terms: 29 + -1 = 28 7 + 4a = 54(28) Multiply 54 * 28 7 + 4a = 1512 Solving 7 + 4a = 1512 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4a = 1512 + -7 Combine like terms: 7 + -7 = 0 0 + 4a = 1512 + -7 4a = 1512 + -7 Combine like terms: 1512 + -7 = 1505 4a = 1505 Divide each side by '4'. a = 376.25 Simplifying a = 376.25
| 0.1x-0.2(3-2x)=-0.7(x-6) | | ht=16t^2+72t+40 | | 2(3x+1)-6=2(x+2) | | 2(6-2y)=4y-8 | | Ht=-16t+72t+40 | | 3/5(2x+8)=2(2-3x)+8 | | 20=-2j | | m/3-4=11 | | 1/3X+3+1/5X-1/3 | | y+10/7=-2 | | 1/2(y-1)+6=7/8(5y-7) | | 7X=1+22 | | (15)-25-18= | | 7(2x+1)+6(x+3)= | | 0.3(1.2X-3.6)=4.2X-16.44 | | 10-1/10x=1/15x | | 88=-9q+16 | | 3t+12= | | x/5+5=5 | | p/9+38=41 | | y=3x^2-6x+4 | | 3(-X-7)=-2(2X+5) | | 21+45=x-65 | | c/2+2=3 | | 55=3(2x-3)-1 | | 5+3x/2 | | -3d+1=4 | | 2(x-6)-13= | | 2(3Z-5)+2=4Z-3(2Z+8) | | 4(x-3)x=x-6 | | x^4+x^2-72=0 | | 15,000/342 |